Terrorist assassination and institutional change in repressive regimes - Bell, Laura N. (Terrorism and political violence, 2019)
Missing from the political violence literature is an in-depth and systematic examination of the effects of terrorist assassination on state political institutions in repressive regimes. By broadening the scope and depth of empirical research into terrorist assassinations, the potential exists to enhance our understanding of the outcomes of assassination by terrorist actors as well as our overall understanding of political violence in repressive regimes. Utilizing survival analysis and data from the Global Terrorism Database, the Polity IV Project, and the Political Terror Scale, this project focuses on the post-terrorist assassination institutional outcomes in repressive regimes. While the effects are long-term, the most repressive regimes are the most likely to experience political institutional shifts in the wake of terrorist assassinations. The direction of the institutional shifts is mixed, but results indicate that the level of state repression in existence prior to a terrorist assassination matters to post-terrorist assassination outcomes.